Perancangan dan Implementasi Database Pada Sistem Informasi Absensi Mahasiswa Berbasis Digital untuk Meningkatkan Efisiensi Pengelolaan Data - Alwi Sampariji; Muhammad Irwan Padli Nasution (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The advancement of information technology has driven significant transformation in administrative systems within higher education institutions, including the management of student attendance. Manual attendance systems still used by some institutions have several fundamental weaknesses, such as susceptibility to recording errors (human error), potential for data manipulation, slow recapitulation processes, and overall inefficiency in information management. Therefore, a digital-based solution capable of automating the recording and management of attendance data is needed. This study aims to design and implement a database for a digital-based student attendance information system to improve efficiency, accuracy, and integrity in academic data management. The research methods employed include system requirements analysis, Entity Relationship Diagram (ERD) design as a conceptual representation of the database, and table normalization up to the third normal form (3NF). The results indicate that the designed database system is capable of integrating all major data entities, namely student data, lecturer data, courses, class schedules, and attendance records, in a structured and relational manner. The implementation of this database system facilitates data management, improves information access speed, and minimizes recording errors that have long been a weakness of manual systems.